Gender approach in the peruvian justice system and the rights of women victims of family violence - Dongo Esquivel, Hiancarla Margriet (2022)
Gender stereotypes are analyzed within a Peruvian criminal process referred to crimes of family violence, that is, injuries due to family violence and assault against women and members of the family group, in order to establish or not the compensation of the rights of the victims, who are generally women, and obtain a comprehensive view of the social phenomenon based on the principle of material equality and non-discrimination, as well as the effects of stereotypes in the administration of justice, all this in the Judicial District of Apurímac.